EFEK INTELECTUAL CAPITAL (IC) PADA MOTIVASI PERILAKU WINDOW DRESSING LAPORAN KEUANGAN PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Heni Yusnita, M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study was to examine the effect of intellectual capital on the motivation for window dressing behavior in financial statements in transportation companies listed on the Indonesia Stock Exchange. This study uses primary data obtained by filling out a questionnaire. The population in this study are all transportation companies listed on the Indonesia Stock Exchange in 2021 as many as 47 companies with a sample of 20 companies. The data analysis technique used in this study uses Structural Equation Modeling (SEM) with Smart PLS (Partial Least Square) software. The results of the study: 1. Human capital has an effect on the motivation of window dressing behavior, 2. Structural capital has no effect on the motivation of window dressing behavior, 3. Relational capital has an effect on the motivation of window dressing behavior